2013
DOI: 10.1590/s0103-05822013000100014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da participação de mães em um programa de prevenção e controle de cáries e doenças periodontais para lactentes

Abstract: OBJETIVO: Avaliar o conhecimento sobre saúde bucal de mães participantes de um programa educativo-preventivo para lactentes. MÉTODOS: Estudo de coorte com 112 mães e seus bebês de 0 a 18 meses, cadastrados no projeto "Promoção de Saúde Bucal na Primeira Infância", da Universidade Federal do Maranhão. Inicialmente, entrevistas semiestruturadas que contemplavam o nível de conhecimento das mães sobre a saúde bucal dos bebês foram realizadas. Também foi examinada a cavidade bucal dos bebês a fim de detectar o níve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
3
0
2
Order By: Relevance
“…These data are similar to those of a recent study that also did not observe changing in dietary habits after educative-preventive following-up [22]. Based on these results, the shift to a healthy diet is a difficult goal to be reached because dietary habits are related to cultural values and socioeconomic level of the family, as well as the education level of the parents [2,23], making difficult the changing in the behavior.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These data are similar to those of a recent study that also did not observe changing in dietary habits after educative-preventive following-up [22]. Based on these results, the shift to a healthy diet is a difficult goal to be reached because dietary habits are related to cultural values and socioeconomic level of the family, as well as the education level of the parents [2,23], making difficult the changing in the behavior.…”
Section: Discussionsupporting
confidence: 87%
“…After the program, 19 (57.57%) infants changed oral hygiene habits. A similar study observed that firstly 57.3% of the mother performed the oral hygiene of the children twice per day and 42.7% once per day; after the educative-preventive advice the percentage changed to 74.7% and 24.1%, respectively [22]. These data supported the hypothesis that educative activities can be effective in the consciousness and instruction of the parents by encouraging them to greater dedication to the oral health of their children [26], especially when these stimuli do not require substantial changes, such as diet.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, it is suggested that greater attention should be given to the need for early oral hygiene. ( 18 ) Positive results are observed when mothers are informed after birth of their children. In a longitudinal study, 480 mothers of children aged 6 to 18 months were randomly selected from a primary healthcare unit, in which the use of the nighttime baby bottle was noted only in the group that did not receive orientations regarding oral health (control group).…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados do GO se aproximaram dos encontrados no estudo de Silva et al (2013), em que após a atividade educativa com as mães, todas as crianças passaram a fazer a escovação diária e a realizavam duas vezes ao dia (74,7%).…”
Section: Discussionunclassified
“…Pais demonstram conhecimentos limitados sobre odontologia na primeira infância, bem como desconhecem o risco de crianças pequenas desenvolverem doenças como a cárie dentária (FERREIRA et al, 2010), contudo, a literatura (STOCCO e BALDANI, 2011;VIEIRA e KARBAGE, 2011;SILVA et al, 2013) mostra que, quando ocorre intervenções educativas com mães e cuidadores acerca da importância dos aspectos nutricionais, dietéti-cos, higiênicos e outros relativos aos cuidados básicos de saúde bucal tende a resultar em uma redução desta doença. O aparecimento da cárie em crianças de baixa idade está, em geral, diretamente relacionado à desinformação dos pais e responsáveis (BRASIL, 2012).…”
unclassified